(untitled) (International Journal of Engineering and Computer Science, 2017)
The premise of this research idea is to develop smart health centers in India. The proposal basically exploits the idea of Internet of things and aims to use the existing technology and background. The work has been motivated by the fact that India is lacking in terms of number of health centers corresponding to the population of country and in villages especially. More prominently if a health center is available, Doctors generally either are not willing to serve the rural areas or they are not available 24x7 leading to rural population turning to cities even for casual ailments. This adds to long queues in hospitals and lot of annoyance to patients. In order to avoid above mentioned limitations, the proposed model aims to address the patient without even physically visiting the health center and also prescription can be generated in the absence of Doctor. It is expected that such a smart system would not only facilitate sick but also will add prosperity indirectly to villages. The proposed framework would definitely bring a significant change in the health care sector of India.